Towards the Anaerobic Production of Surfactin Using Bacillus subtilis - Hoffmann, Mareen; Fernandez Cano Luna, Diana Stephanie; Xiao, Shengbin; Stegemüller, Lars; Rief, Katharina; Heravi, Kambiz Morabbi; Lilge, Lars; Henkel, Marius; Hausmann, Rudolf (Frontiers in Bioengineering and Biotechnology, 2020)
The anaerobic growth of B. subtilis to synthesize surfactin poses an alternative strategy to conventional aerobic cultivations. In general, the strong foam formation observed during aerobic processes represents a major obstacle. Anaerobic processes have, amongst others, the distinct advantage that the total bioreactor volume can be exploited as foaming does not occur. Recent studies also reported on promising product per biomass yields. However, anaerobic growth in comparison to aerobic processes has several disadvantages. For example, the overall titers are comparably low and cultivations are time-consuming due to low growth rates. B. subtilis JABs24, a derivate of strain 168 with the ability to synthesize surfactin, was used as model strain in this study. Ammonium and nitrite were hypothesized to negatively influence anaerobic growth. Ammonium with initial concentrations up to 0.2 mol/L was shown to have no significant impact on growth, but increasing concentrations resulted in decreased surfactin titers and reduced nitrate reductase expression. Anaerobic cultivations spiked with increasing nitrite concentrations resulted in prolonged lag-phases. Indeed, growth rates were in a similar range after the lag-phase indicating that nitrite has a neglectable effect on the observed decreasing growth rates. In bioreactor cultivations, the specific growth rate decreased with increasing glucose concentrations during the time course of both batch and fed-batch processes to less than 0.05 1/h. In addition, surfactin titers, overall YP/X and YP/S were 53%, ~42% and ~57% lower than in serum flask with 0.190 g/L, 0.344 g/g and 0.015 g/g. The YX/S, on the contrary, was 30% lower in the serum flask with 0.044 g/g. The productivities q were similar with ~0.005 g/(g∙h). However, acetate strongly accumulated during cultivation and was posed as further metabolite that might negatively influence anaerobic growth. Acetate added to anaerobic cultivations in a range from 0 g/L up to 10 g/L resulted in a reduced maximum and overall growth rate µ by 44% and 30%, respectively. To conclude, acetate was identified as a promising target for future process enhancement and strain engineering. Though, the current study demonstrates that the anaerobic cultivation to synthesize surfactin represents a reasonable perspective and feasible alternative to conventional processes.